Heat transfer performance assessment for precise accelerated control cooling of the hot heavy clad plate. (May 2023) - Ok, Jung Soo; Lim, Hwan Suk; Kim, Seonggon; Kang, Yong Tae
Abstract: In this study, the heat transfer characteristics are estimated to determine the internal temperature distribution of the hot heavy clad plate from the measured surface temperature prior to the accelerated control cooling process. The temperature prediction accuracy is verified by the advanced inverse heat transfer method (A-IHTM). It is found that the plate temperature distribution can be considered with the quasi-equilibrium state within the temperature deviation rate of 0.1 °C / s . The results have been also verified through a comparison with an analytical method over time, using dimensionless surface temperature. The comparison yielded a standard deviation of 0.027 and root mean squared error (RMSE) of 0.0574 in dimensionless temperature, indicating that the numerical method is a viable option for accurately predicting the temperature distribution in the hot heavy clad plate during the accelerated control cooling process. The internal temperature distribution of the heavy plate changes non-linearly. This phenomenon is defined as the "heat capacity effect" considering the enthalpy change. With the heat transfer characteristics, the cooling process of heavy clad plate could be controlled within finish cooling temperature deviation of 14.7 °C, cooling rate deviation of 0.7 °C / s . Also, the cooling control accuracy for the finish cooling temperature can be improved by 12.6 % with the satisfied mechanical property of heavy clad plate for corrosion resistance.